Prevalence of Aflatoxin B1 in Commercial Dried Fish from Some Regions of Java - Ninoek Indriati; Irma Hermana; Izhamil Hidayah; Endang Sri Rahayu (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
The purpose of this study is to study the prevalence of aflatoxin B1 in commercial dried salted fish and other related information. A total of 150 samples were classified into 3 groups, based on the salt content. Low salt content (0-5%) were dried anchovies (Stolephorus sp.) and commerson’s anchovy (Stolephorus commersonii); moderate salt content (6-10%) were medan anchovy (Stolephorus bataviensis) and  whipfin silverbiddy (Gerres filamentosus) while high salt content (10%) were moonlight gouramy (Trichogaster microlepis) and snakehead fish (Channa striata). The samples were collected from different seller in Java Island and then determined for Aspergillus flavus, Aflatoxin B1, salt content, moisture content, pH, water activity and total mold count. Results showed that dried salted fish were contaminated with A. flavus at temperature of 25.2-32.2 oC, 65-84% humidity, 17-50% moisture content, 0.25-19.88% salt content, and 0.73-0.86 aw. The prevalence of A. flavus in dried salted fish was 9.33% (14/150) and the prevalence of aflatoxin B1 was 8% (12/150) with detectable concentrations of 10.71-33.6 ppb.